Development of Web Based Learning Material in Physics Subject for Kalor and Temperature Material - Fatwa Aji Kurniawan; Sulhadi S; Agus Yulianto (Department of Physics, Sebelas Maret University, 2015)
It has been done, the research which aims to develop a web-based teaching materials on the subjects of physics subject with subject mater of temperature and heat. This study using a modified model of the 4D development by eliminating the deployment phase. The validation of product development conducted by validator media experts and experts matter of physics, whereas small-scale trials conducted by physics teacher and 10 students. Validator review results stating that the quality of the product development were included in the category very well with the average percentage rating of 83.93%. The percentage value assigned by media expert by 75% in the good category and the percentage of the value provided by a matter expert 92.85% were in the very good category. Experiments by physics teacher to obtain result of equal to 94.44% were in the very good category and the average percentage of the test results by the students of 90.5% were in the very good category. The characteristics of the products developed include material composition using the curriculum in 2013, there was a recording facility and the results of evaluation of students' activities, there were feedback evaluation results were immediately known by the students and there were some links related to the material either youtube or other learning website.